Preparation method and application of electrocatalytic active anode film capable of efficiently producing active chlorine
By growing a modified titanium dioxide nanoarray tube on a porous titanium substrate and loading a RuO2 catalytic layer to form an electrocatalytic active anode film, the problems of low stability and efficiency of electrode materials in the existing electrocatalytic oxidation technology are solved, and efficient production of active chlorine and excellent pollutant degradation effects are achieved.
Patent Information
- Application Number
- CN202411642695.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
When existing electrocatalytic oxidation technology treats printing and dyeing wastewater, the stability and efficiency of electrode materials are low, resulting in insufficient production of active chlorine and low pollutant degradation efficiency.
A porous titanium substrate is used as the electrode material, and a modified titanium dioxide nanoarray tube and a supported RuO2 catalytic layer are grown on its surface to form an electrocatalytic active anode film. The film improves the bonding force between the catalyst and the substrate and the conductivity of the material through two anodization and cathode reduction treatments.
It significantly improves the production of active chlorine and the degradation efficiency of organic pollutants, overcomes the problem of mass transfer limitation, and improves the mechanical strength and electron transfer rate of the electrode.
Smart Images

Figure CN119503970A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic oxidation, and in particular relates to a method for preparing an electrocatalytic active anode membrane for efficiently producing active chlorine and an application thereof. Background Art
[0002] China is a major textile industry country, and the textile printing and dyeing industry is one of the important pillars of the country's traditional economy. In the printing and dyeing process, various inorganic salts, surfactants, etc. are often added to effectively improve the coloring rate and fixation effect of dyes in textiles. These inorganic salts added in large quantities in the printing and dyeing process have caused the salinity of the production wastewater to increase, which is often called "printing and dyeing saline wastewater". In addition to high salinity, "printing and dyeing saline wastewater" also has the characteristics of large chromaticity, complex components, high toxicity, and low biodegradability. It is a complex and difficult-to-degrade industrial wastewater that will cause serious pollution to the environment.
[0003] For this type of complex water, common traditional treatment methods include physical methods (adsorption, flotation and other technologies), chemical methods (coagulation, flocculation and other technologies) and biological methods. However, physical methods cannot completely mineralize and remove pollutants such as dyes, and adsorption methods will produce a large amount of sludge, resulting in secondary pollution; chemical methods require the addition of a large amount of chemical agents, resulting in a significant increase in costs; biological methods are currently the most mature method for treating printing and dyeing wastewater pollution, and are effective in reducing COD and turbidity, but the decolorization effect is relatively poor, and the higher salinity in "printing and dyeing salt-containing wastewater" will inhibit microbial metabolism, limiting the application of biological methods.
[0004] Electrochemical oxidation technology (EAOP) has attracted much attention in the field of printing and dyeing wastewater treatment because of its mild conditions, the ability to use electrons instead of oxidizing / reducing agents, and the avoidance of reagent addition; it can generally be carried out at room temperature and pressure; the electrochemical reaction device is relatively simple and can be flexibly designed according to water quality conditions. In addition, EAOP can utilize the high concentration of inorganic salt ions in "printing and dyeing salt-containing wastewater" to treat the wastewater with Cl - The inorganic salt ions represented by act as electrolytes, generating a series of active chlorine (Cl 2 、HClO、ClO - etc.), can effectively oxidize the dye to decolorize and degrade, achieving a better decolorization effect.
[0005] One of the key points and difficulties in electrochemical oxidation wastewater treatment is to develop more stable and efficient electrode materials. Metal oxide electrodes are a type of material with stable properties and strong mechanical properties. Metal oxide coated electrodes (DSA electrodes) with low-cost titanium as the substrate are usually loaded with a layer of RuO on the surface of the titanium substrate. 2 、IrO 2 , PbO 2Such electrodes have the characteristics of high electrocatalytic activity and low economic cost, and are excellent anode materials in the field of electrocatalysis. Among them, RuO 2 It has a low chlorine evolution potential. When treating chlorine-containing organic wastewater, the conversion of chloride ions in water is relatively simple, the active chlorine yield is high, and it shows an excellent chlorine evolution effect. However, due to the limitation of the foam titanium substrate, the catalyst coating has poor bonding with the substrate and is easy to fall off, resulting in electrode deactivation and inability to operate for a long time. Furthermore, due to the low diffusion control rate of the traditional operation mode (Flow-by) and the thick mass transfer boundary layer (>100μm), the application and development of EAOP in the field of deep sewage treatment are also limited. Summary of the invention
[0006] In view of this, the object of the present invention is to provide an electrocatalytically active anode membrane that can efficiently generate active chlorine species, which can be applied in a continuous flow system, can effectively improve the mass transfer performance and has a high degradation efficiency for organic pollutants.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides an electrocatalytically active anode film, comprising a porous titanium substrate, a modified titanium dioxide nano-array tube grown on the surface of the porous titanium substrate, and RuO 2 Catalytic layer;
[0009] The modified titanium dioxide nanotube array comprises anatase titanium dioxide nanotube array and Ti doped in the anatase titanium dioxide nanotube array by a cathode reduction method. 3+ ;
[0010] Preferably, the inner diameter of the anatase titanium dioxide nano-array tube is 20 to 100 nm, the outer diameter is 50 to 200 nm, and the length is 2.0 to 4.0 μm.
[0011] The present invention also provides a method for preparing the electrocatalytically active anode film described in the above technical solution, comprising the following steps:
[0012] The porous titanium substrate is immersed in an acidic solution for acidification to obtain a pretreated substrate;
[0013] The acidified porous titanium substrate is placed in a first anodizing solution for a first anodizing, and the oxidized porous titanium substrate is placed in deionized water for ultrasonic treatment to obtain a pre-oxidized porous titanium substrate; the pre-oxidized foamed titanium substrate is placed in a second anodizing solution for a second anodizing, and ultrasonic treatment and vacuum drying are performed to obtain a native Ti / TiO 2 NTAs;
[0014] The native Ti / TiO 2 NTAs were calcined to obtain Ti / TiO 2 NTAs;
[0015] The Ti / TiO 2 NTAs were placed in a reducing solution for cathode reduction and vacuum dried to obtain r-TiO 2 NTAs;
[0016] The r-TiO 2 NTAs are placed in RuO 2 After the precursor solution was allowed to stand and dried under vacuum, RuCl 3 r-TiO 2 NTAs;
[0017] The RuCl 3 r-TiO 2 NTAs are calcined to obtain the RuO 2 @r-TiO 2 NTAs electrocatalytically active anodic film;
[0018] The acidification pretreatment solution comprises an inorganic acid and water;
[0019] The first anodizing solution and the second anodizing solution are composed of a soluble fluorine source, ethylene glycol and water;
[0020] The reducing solution comprises an inorganic acid and water;
[0021] The RuO 2 The precursor solution comprises a soluble ruthenium source and water;
[0022] Preferably, the acid pretreatment solution comprises hydrofluoric acid, nitric acid and water; the volume ratio of hydrofluoric acid to nitric acid is 1:2-5, and the volume ratio of hydrofluoric acid to water is 1:5-30; the temperature for the acid pretreatment is 20-40°C, and the pretreatment time is 10-60s;
[0023] Preferably, the electrolyte solution for the first anodic oxidation comprises ammonium fluoride, ethylene glycol and water; the mass ratio of ammonium fluoride to water in the electrolyte solution for the first anodic oxidation is 1:3-6, and the mass ratio of ammonium fluoride to ethylene glycol is 1:100-400; the temperature for the first anodic oxidation is 20-35°C, the oxidation time is 0.5-10h, the oxidation voltage is 20-100V, the cathode comprises graphite, titanium sheet or platinum sheet, and the plate spacing is 1-4cm;
[0024] Preferably, the electrolyte solution for the second anodic oxidation comprises ammonium fluoride, ethylene glycol and water; the mass ratio of ammonium fluoride to water in the electrolyte solution group for the second anodic oxidation is 1:2-5, and the mass ratio of ammonium fluoride to ethylene glycol is 1:200-600; the temperature for the second anodic oxidation is 20-35°C, the oxidation time is 0.5-10h, the oxidation voltage is 20-100V, the cathode comprises graphite, titanium sheet or platinum sheet, and the plate spacing is 1-4cm;
[0025] Preferably, the calcination temperature is 250-500° C., the heating rate to the calcination temperature is <10° C. / min, and the holding time is 0.5-6 h.
[0026] Preferably, the electrolyte solution for the cathode reduction reaction comprises concentrated sulfuric acid and water; the molar concentration of the reducing solution is 0.1-0.5 mol / L; the temperature for the cathode reduction is 20-40°C, the reduction time is 1-20 min, and the reduction current density is 1-10 mA / cm 2 , the cathode includes graphite, titanium sheet or platinum sheet, and the distance between the plates is 1 to 4 cm;
[0027] Preferably, the soluble ruthenium source in the precursor solution includes ruthenium chloride trihydrate; the concentration of the soluble ruthenium source in the precursor solution is 5 to 20 mmol / L;
[0028] Preferably, the load temperature of the precursor solution is 20 to 40° C., and the load time is 12 to 48 hours;
[0029] Preferably, the calcination temperature is 250-500° C., the heating rate to the calcination temperature is <10° C. / min, and the holding time is 0.5-6 h.
[0030] The present invention also provides the use of the electrocatalytically active anode membrane described in the above technical solution or the electrocatalytically active anode membrane prepared by the preparation method described in the above technical solution in continuous flow (Flow-through) treatment of organic wastewater.
[0031] The present invention provides an electrocatalytically active anode film, comprising a porous titanium substrate and a modified titanium dioxide nano-array tube grown on the surface of the porous titanium substrate; the modified titanium dioxide nano-array tube comprises a calcined titanium dioxide nano-array tube, a Ti doped in the titanium dioxide nano-array tube, and a 3+ and RuO loaded on the titanium dioxide nano-array tube 2 .
[0032] The present invention uses porous foam titanium as a substrate, removes the surface oxide layer through acidification pretreatment, and in-situ grows a highly ordered titanium dioxide nanotube array as an intermediate layer on the substrate through a double anodic oxidation method, which effectively improves the bonding force between the catalyst and the substrate, increases the specific surface area, and also enhances the mechanical strength and electron transfer rate of the material; at the same time, the TiO 2 Ti 4+ Partially converted to Ti 3+ , Ti 3+ The doping of can effectively improve the conductivity of the material; at the same time, RuO is loaded on the titanium dioxide nanotube array, which can reduce the chlorine evolution potential and thus produce more active chlorine. 2 , thereby improving the degradation efficiency of the anode membrane for organic pollutants. The prepared anode membrane has a porous structure. When applied to a continuous flow system, it can increase the active chlorine production and the contact oxidation efficiency of pollutants at the anode membrane interface, overcoming the mass transfer limitation problem.
[0033] The electrocatalytically active anode film provided by the present invention overcomes the defect that the porous titanium substrate and the metal oxide coating are not firmly bonded, and at the same time has excellent electrocatalytic activity. The process flow of the present invention is simple and the reaction conditions are mild, which is expected to expand the application of active DSA electrodes in the field of water pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The r-TiO obtained in Example 1 2 NTAs and RuO 2 @r-TiO 2 XRD patterns of NTAs;
[0035] Figure 2 The Ti / TiO obtained in Example 2 2 SEM images of NTAs;
[0036] Figure 3 The Ti / TiO obtained in Example 2 2 SEM images of the cross section of NTAs;
[0037] Figure 4 The r-TiO obtained in Example 1 2 NTAs and RuO 2 @r-TiO 2 Cyclic voltammograms of NTAs;
[0038] Figure 5 Schematic diagram of a continuous flow (Flow-through) device of the present invention;
[0039] Figure 6The active chlorine production diagram of Example 1 in batch (Flow-by) and continuous flow (Flow-through) modes;
[0040] Figure 7 The RuO obtained in Example 1 2 @r-TiO 2 Decolorization test results of Congo red contaminant solution by NTAs in different modes;
[0041] Figure 8 The RuO obtained in Example 1 2 @r-TiO 2 Decolorization test results of Congo red pollutant solution by NTAs at different current densities;
[0042] Fig. 9 The RuO obtained in Example 1 2 @r-TiO 2 NTAs decolorization test results of Congo red pollutant solutions at different initial pollutant concentrations. DETAILED DESCRIPTION
[0043] The present invention provides an electrocatalytically active anode film, comprising a porous titanium substrate, a modified titanium dioxide nano-array tube grown on the surface of the porous titanium substrate, and RuO 2 Catalytic layer;
[0044] The modified titanium dioxide nanotube array comprises an anatase titanium dioxide nanotube array and Ti doped in the anatase titanium dioxide nanotube array by a cathode reduction method. 3+ ;
[0045] In the present invention, the inner diameter of the titanium dioxide nanotube array is 20 to 100 nm, the outer diameter is 50 to 200 nm, and the length is 2.0 to 4.0 μm; the inner diameter is further preferably 40 to 80 nm, more preferably 45 to 60 nm; the outer diameter is further preferably 50 to 150 nm, more preferably 90 to 140 nm; the length is further preferably 2.5 to 3.5 μm, more preferably 2.5 to 3.1 μm.
[0046] The present invention also provides a method for preparing the electrocatalytically active anode film described in the above technical solution, comprising the following steps:
[0047] The porous titanium substrate is immersed in an acidic solution for acidification to obtain a pretreated substrate;
[0048] The acidified porous titanium substrate is placed in a first anodizing solution for a first anodizing, and the oxidized porous titanium substrate is placed in deionized water for ultrasonic treatment to obtain a pre-oxidized porous titanium substrate; the pre-oxidized foamed titanium substrate is placed in a second anodizing solution for a second anodizing, and ultrasonic treatment and vacuum drying are performed to obtain a native Ti / TiO 2 NTAs;
[0049] The native Ti / TiO 2 NTAs were calcined to obtain Ti / TiO 2 NTAs;
[0050] The Ti / TiO 2 NTAs were placed in a reducing solution for cathode reduction and vacuum dried to obtain r-TiO 2 NTAs;
[0051] The r-TiO 2 NTAs are placed on RuO 2 After the precursor solution was allowed to stand and dried under vacuum, RuCl 3 r-TiO 2 NTAs;
[0052] The RuCl 3 r-TiO 2 NTAs are calcined to obtain the RuO 2 @r-TiO 2 NTAs electrocatalytically active anodic film;
[0053] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0054] The present invention immerses the porous titanium substrate in an acidic solution for acidification treatment to obtain an acidification pretreated substrate;
[0055] In the present invention, the porous titanium substrate is preferably porous foamed titanium. In the present invention, the pore size of the porous titanium substrate is preferably 20 μm;
[0056] In the present invention, the composition of the acid pretreatment solution preferably includes hydrofluoric acid, nitric acid and water; the volume ratio of hydrofluoric acid to nitric acid is preferably 1:2-5, and the volume ratio of hydrofluoric acid to water is preferably 1:5-30; the temperature for the acid pretreatment is preferably 20-40°C, and the pretreatment time is preferably 10-60s;
[0057] The present invention places the acidified porous titanium substrate in a first anodizing solution for first anodizing, places the oxidized porous titanium substrate in deionized water, and performs ultrasonic treatment to obtain a pre-oxidized porous titanium substrate; places the pre-oxidized foamed titanium substrate in a second anodizing solution for second anodizing, performs ultrasonic treatment and vacuum drying to obtain a native Ti / TiO 2 NTAs;
[0058] In the present invention, the electrolyte solution composition for the first anodic oxidation preferably includes ammonium fluoride, ethylene glycol and water; the mass ratio of ammonium fluoride to water in the electrolyte solution group for the first anodic oxidation is preferably 1:3-6, and the mass ratio of ammonium fluoride to ethylene glycol is preferably 1:100-400; the temperature for the first anodic oxidation is preferably 20-35°C, the oxidation time is preferably 0.5-10h, the oxidation voltage is preferably 20-100V, the cathode preferably includes graphite, titanium sheet or platinum sheet, and the plate spacing is preferably 1-4cm;
[0059] In the present invention, the ultrasonic treatment is preferably carried out in deionized water, the power is preferably 180W, and the time is preferably 5 to 30 minutes. In the present invention, the carbon dioxide nanoarray tubes grown on the surface by the first anodization can be peeled off by ultrasonic treatment, and the carbon dioxide nanoarray tube growth sites are left, providing a template basis for the subsequent second anodization.
[0060] In the present invention, the electrolyte solution composition for the second anodic oxidation preferably includes ammonium fluoride, ethylene glycol and water; the mass ratio of ammonium fluoride to water in the electrolyte solution group for the second anodic oxidation is preferably 1:2-5, and the mass ratio of ammonium fluoride to ethylene glycol is preferably 1:200-600; the temperature for the second anodic oxidation is preferably 20-35°C, the oxidation time is preferably 0.5-10h, the oxidation voltage is preferably 20-100V, the cathode preferably includes graphite, titanium sheet or platinum sheet, and the plate spacing is preferably 1-4cm;
[0061] In the present invention, the ultrasonic treatment is preferably carried out in anhydrous ethanol and deionized water in sequence, the power of the ultrasonic treatment is preferably 180W, the anhydrous ethanol ultrasonic treatment time is preferably 5 to 30 minutes, and the deionized water ultrasonic treatment time is preferably 5 to 30 minutes. In the present invention, the electrolyte solution remaining on the surface and inside of the electrode can be removed by ultrasonic treatment in ethanol and deionized water.
[0062] In the present invention, the vacuum drying temperature is preferably 60 to 100° C., and the vacuum drying time is preferably 6 to 24 hours.
[0063] In the present invention, the performance of the titanium dioxide nanotube array and its bonding strength with the porous titanium substrate can be effectively improved by performing two anodic oxidations.
[0064] The present invention converts the native Ti / TiO 2 NTAs were calcined to obtain Ti / TiO 2 NTAs;
[0065] In the present invention, the calcination temperature is preferably 250-500°C, more preferably 300-400°C, and more preferably 350-400°C; the heating rate to the calcination temperature is preferably <10°C / min, and more preferably 5°C / min; the holding time is 0.5-6h, more preferably 1-5h, and more preferably 2-4h.
[0066] In the present invention, the calcination is preferably carried out in an air atmosphere. In the present invention, the calcination is preferably carried out in a tube furnace.
[0067] The present invention comprises the Ti / TiO 2 NTAs were placed in a reducing solution for cathode reduction and vacuum dried to obtain r-TiO 2 NTAs;
[0068] In the present invention, the electrolyte solution composition of the cathode reduction reaction preferably includes concentrated sulfuric acid and water; the molar concentration of the reducing solution is preferably 0.1-0.5 mol / L; the temperature for the cathode reduction is preferably 20-40°C, the reduction time is preferably 1-20 min, and the reduction current density is preferably 1-10 mA / cm 2 The cathode preferably comprises graphite, titanium sheet or platinum sheet, and the distance between the plates is preferably 1 to 4 cm;
[0069] In the present invention, the vacuum drying temperature is preferably 60 to 100° C., and the vacuum drying time is preferably 6 to 24 hours.
[0070] The present invention uses r-TiO 2 NTAs are placed on RuO 2 The precursor solution was allowed to stand and then dried under vacuum to obtain RuCl 3 r-TiO 2 NTAs;
[0071] In the present invention, the soluble ruthenium source in the precursor solution is preferably ruthenium chloride trihydrate; the concentration of the soluble ruthenium source in the precursor solution is preferably 5 to 20 mmol / L; the load temperature of the precursor solution is preferably 20 to 40° C.; the load time is preferably 12 to 48 hours;
[0072] In the present invention, the vacuum drying temperature is preferably 60 to 100° C., and the vacuum drying time is preferably 6 to 24 hours.
[0073] The present invention loads RuCl 3 r-TiO 2 NTAs are calcined to obtain the RuO 2 @r-TiO 2 NTAs electrocatalytically active anodic films.
[0074] In the present invention, the calcination temperature is preferably 250-500°C, more preferably 300-450°C, and more preferably 300-400°C; the heating rate to the calcination temperature is preferably <10°C / min, and more preferably 5°C / min; the holding time is 0.5-6h, more preferably 1-5h, and more preferably 2-4h.
[0075] In the present invention, the calcination is preferably carried out in an air atmosphere. In the present invention, the calcination is preferably carried out in a tube furnace.
[0076] The present invention also provides the use of the electrocatalytically active anode membrane described in the above technical solution or the electrocatalytically active anode membrane prepared by the preparation method described in the above technical solution in continuous flow (Flow-through) treatment of organic wastewater.
[0077] In order to further illustrate the present invention, an electrocatalytically active anode membrane provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0078] Example 1
[0079] A porous titanium foam with a pore size of 20 μm was placed in a mixed acid solution (wherein, hydrofluoric acid: nitric acid: water = 1:3:21), allowed to stand at 25°C for 30 seconds, then taken out, placed in anhydrous ethanol and deionized water for ultrasonic cleaning for 10 minutes and 15 minutes respectively, and then placed in a vacuum drying oven at 80°C for 8 hours to obtain an acidified porous titanium substrate;
[0080] Take 2.5g of ammonium fluoride and dissolve it in 10mL of deionized water, add ethylene glycol to make up to 500mL, and obtain the first anodizing solution. Use the acidified porous titanium substrate as the anode, the graphite electrode as the cathode, the plate spacing is 3cm, the temperature is 30℃, and the anodizing is carried out at 60V voltage for 1h. Place the oxidized electrode in deionized water for ultrasonication for 15min, and the ultrasonic power is set to 180W to obtain a pre-oxidized porous titanium substrate;
[0081] Take 1.0g of ammonium fluoride and dissolve it in 5mL of deionized water, add ethylene glycol to make it up to 500mL, and obtain the second anodizing solution. The pre-oxidized porous titanium substrate is used as the anode, the graphite electrode is used as the cathode, the plate spacing is 3cm, the temperature is 30℃, and the anodizing is carried out at a voltage of 60V for 4h. The oxidized electrodes are placed in anhydrous ethanol and deionized water for ultrasonic treatment for 10min, the ultrasonic power is set to 180W, and then placed in a vacuum drying oven for drying at 80℃ for 12h to obtain the native Ti / TiO 2 NTAs;
[0082] The original Ti / TiO 2 NTAs were placed in a tube furnace and calcined in air atmosphere. The temperature was raised to 350°C at a heating rate of 5°C / min and kept at this temperature for 2h to obtain Ti / TiO 2 NTAs;
[0083] Take 1.103 mL of 18.4 mol / L concentrated sulfuric acid, add deionized water to make up to 100 mL, and ultrasonicate for 5 min to obtain 0.2 mol / L sulfuric acid reduction solution;
[0084] Ti / TiO 2 NTAs was placed in the reducing solution as the cathode, with a platinum electrode as the anode, the plate spacing was 3 cm, the temperature was 30 °C, and the current was 3 mA / cm 2 The cathode reduction was carried out at a current density of 10 min to obtain r-TiO 2 NTAs;
[0085] Take 0.1035g of ruthenium chloride trihydrate, dilute to 50mL with deionized water, and ultrasonically disperse for 5min to obtain a ruthenium precursor aqueous solution. 2 NTAs were placed in a 25°C precursor aqueous solution in the dark for 24 hours, and then dried in a vacuum oven at 80°C for 12 hours. The dried electrode was placed in a tube furnace and calcined in an air atmosphere at a heating rate of 5°C / min to 350°C, and kept at this temperature for 1 hour to finally obtain RuO 2 @r-TiO 2 NTAs electrocatalytically active anodic films.
[0086] Example 2
[0087] A porous titanium foam with a pore size of 20 μm was placed in a mixed acid solution (wherein, hydrofluoric acid: nitric acid: water = 1:3:21), allowed to stand at 25°C for 30 seconds, then taken out, placed in anhydrous ethanol and deionized water for ultrasonic cleaning for 10 minutes and 15 minutes respectively, and then placed in a vacuum drying oven at 80°C for 8 hours to obtain an acidified porous titanium substrate;
[0088] Take 2.5g of ammonium fluoride and dissolve it in 10mL of deionized water, add ethylene glycol to make up to 500mL, and obtain the first anodizing solution. Use the acidified porous titanium substrate as the anode, the graphite electrode as the cathode, the plate spacing is 3cm, the temperature is 30℃, and the anodizing is carried out at 60V voltage for 1.5h. Place the oxidized electrode in deionized water for ultrasonication for 15min, and the ultrasonic power is set to 180W to obtain a pre-oxidized porous titanium substrate;
[0089] Take 1.0g of ammonium fluoride and dissolve it in 5mL of deionized water, add ethylene glycol to make it up to 500mL, and obtain the second anodizing solution. The pre-oxidized porous titanium substrate is used as the anode, the graphite electrode is used as the cathode, the plate spacing is 3cm, the temperature is 30℃, and the anodizing is carried out at 60V voltage for 5h. The oxidized electrodes are placed in anhydrous ethanol and deionized water for ultrasonic treatment for 10min, the ultrasonic power is set to 180W, and then placed in a vacuum drying oven for drying at 80℃ for 12h to obtain the original Ti / TiO 2 NTAs;
[0090] The original Ti / TiO 2 NTAs were placed in a tube furnace and calcined in air atmosphere. The temperature was raised to 350°C at a heating rate of 5°C / min and kept at this temperature for 2h to obtain Ti / TiO 2 NTAs;
[0091] Take 1.103 mL of 18.4 mol / L concentrated sulfuric acid, add deionized water to make up to 100 mL, and ultrasonicate for 5 min to obtain 0.2 mol / L sulfuric acid reduction solution;
[0092] Ti / TiO 2 NTAs was placed in the reducing solution as the cathode, with a platinum electrode as the anode, the plate spacing was 3 cm, the temperature was 30 °C, and the current was 3 mA / cm 2 The cathode reduction was carried out at a current density of 10 min to obtain r-TiO 2 NTAs;
[0093] Take 0.1035g of ruthenium chloride trihydrate, dilute to 50mL with deionized water, and ultrasonically disperse for 5min to obtain a ruthenium precursor aqueous solution. 2 NTAs were placed in a 25°C precursor aqueous solution in the dark for 36 hours, and then dried in a vacuum oven at 80°C for 12 hours. The dried electrode was placed in a tube furnace and calcined in an air atmosphere at a heating rate of 5°C / min to 400°C, and kept at this temperature for 1 hour to finally obtain RuO 2 @r-TiO 2 NTAs electrocatalytically active anodic films.
[0094] Characterization and performance testing
[0095] Test Example 1
[0096] Figure 1 The r-TiO obtained in Example 1 2 NTAs and RuO 2 @r-TiO 2 XRD of NTAs; Figure 1 It can be seen that the titanium dioxide nanotube array obtained after calcination is anatase type, and ruthenium is ruthenium dioxide.
[0097] Figure 2 The Ti / TiO obtained in Example 2 2 SEM images of NTAs;
[0098] Figure 3 The Ti / TiO obtained in Example 2 2 SEM images of the cross section of NTAs;
[0099] Figure 4 The r-TiO obtained in Example 1 2 NTAs and RuO 2 @r-TiO 2 Cyclic voltammogram of NTAs; from Figure 4 It can be seen that the electrochemical active area of the material loaded with ruthenium dioxide is larger.
[0100] Figure 5 Schematic diagram of a continuous flow (Flow-through) device of the present invention;
[0101] Test Example 2
[0102] A 0.075M NaCl solution was used as a supporting electrolyte; the electrocatalytically active anode film and porous titanium foam obtained in Example 1 were used as an anode and a cathode, respectively; the distance between the cathode and the cathode was 1 cm;
[0103] The active chlorine production was determined under the conditions of continuous flow (Flow-through) device and beaker (Flow-by) respectively; the electrocatalytic oxidation experiment used a DC power supply (constant current density of 5mA / cm 2 ) was performed; the peristaltic pump in the continuous flow (Flow-through) device provided a flow rate of 20mL / min; the rotor speed in the beaker was set to 100rpm; the aeration volume of the aeration tube was 200mL / min;
[0104] During the test, the solution was collected and analyzed at different times, and the test results were as follows: Figure 6 As shown in Table 1;
[0105] Table 1 Active chlorine production of the electrocatalytically active anode film obtained in Example 1 under different conditions
[0106] Degradation conditions Flow-through Flow-by Active chlorine production (mM) 1.897 0.958
[0107] It can be seen from Table 1 that under the same conditions, the effect of producing active chlorine in the Flow-through mode is greatly improved compared with the Flow-by mode.
[0108] Test Example 3
[0109] A pollutant solution containing Congo red at a concentration of 50 mg / L was prepared, using 0.075 M NaCl solution as the supporting electrolyte;
[0110] The electrocatalytically active anode film and porous titanium foam obtained in Example 1 were used as anode and cathode respectively; the distance between the cathode and cathode was 1 cm;
[0111] Pollutant degradation was performed under the conditions of continuous flow (Flow-through) and beaker (Flow-by) respectively; the electrocatalytic oxidation experiment used a DC power supply (constant current density of 5mA / cm 2 ) was performed; the peristaltic pump in the continuous flow (Flow-through) device provided a flow rate of 20mL / min; the rotor speed in the beaker was set to 100rpm; the aeration volume of the aeration tube was 200mL / min;
[0112] During the test, Congo red solution was collected at different times and analyzed using a UV spectrophotometer. The test results are as follows: Figure 7 As shown in Table 2;
[0113] Table 2 Decolorization effect of the electrocatalytically active anodic film obtained in Example 1 on Congo red
[0114] Degradation conditions Flow-through Flow-by Decolorization rate (%) 92.86 78.26
[0115] It can be seen from Table 2 that under different degradation conditions, the electrocatalytically active anode membrane has the highest decolorization efficiency in the Flow-through mode.
[0116] Test Example 4
[0117] A pollutant solution containing Congo red at a concentration of 50 mg / L was prepared, using 0.075 M NaCl solution as the supporting electrolyte;
[0118] The electrocatalytically active anode film and porous titanium foam obtained in Example 1 were used as anode and cathode, respectively. The cathode and cathode were placed in a continuous flow device, and the peristaltic pump provided a flow rate of 20 mL / min. The distance between the cathode and cathode was 1 cm. The aeration volume of the aeration tube was 200 mL / min. The DC power supply was used to change the current density to 2, 5, and 10 mA / cm in the electrocatalytic oxidation experiment. 2 .
[0119] During the test, Congo red solution was collected and analyzed at different times, and the test results were as follows: Figure 8 As shown in Table 3;
[0120] Table 3 Decolorization effect of the electrocatalytically active anodic film obtained in Example 1 on Congo red
[0121]
[0122] It can be seen from Table 3 that under the same degradation conditions, the comprehensive energy consumption and decolorization effect are good when the current density is 5 mA / cm 2 The effect is best when
[0123] Test Example 5
[0124] Contaminant solutions containing Congo red were prepared at concentrations of 25, 50, and 100 mg / L, respectively, with 0.075 M NaCl solution as the supporting electrolyte;
[0125] The electrocatalytically active anode film and porous titanium foam of Example 1 were used as anode and cathode, respectively; the cathode and cathode were placed in a continuous flow device, the peristaltic pump provided a flow rate of 20 mL / min, and the distance between the cathode and cathode was 1 cm; the aeration volume of the aeration tube was 200 mL / min; a DC power supply (constant current density of 5 mA / cm 2 )conduct.
[0126] During the test, Congo red solution was collected and analyzed at different times, and the test results were as follows: Fig. 9 and as shown in Table 4;
[0127] Table 4 Decolorization effect of the electrocatalytically active anode film obtained in Example 1 on Congo red
[0128]
[0129] It can be seen from Table 4 that under the same degradation conditions, the decolorization effect is not much different when the pollutant concentration is less than 50 mg / L, and can reach more than 90%; when the pollutant concentration reaches 100 mg / L, the decolorization effect decreases slightly, but still reaches more than 80%.
[0130] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An electrocatalytically active anode membrane, characterized in that: It comprises a porous titanium substrate, a modified titanium dioxide nano-array tube grown on the surface of the porous titanium substrate, and a RuO2 catalytic layer; The modified titanium dioxide nanotube array comprises anatase titanium dioxide nanotube array and Ti doped in the anatase titanium dioxide nanotube array by a cathode reduction method. 3+ .
2. The electrocatalytically active anode membrane according to claim 1, characterized in that The inner diameter of the anatase titanium dioxide nanotube array is 20-100 nm, the outer diameter is 50-200 nm, and the length is 2.0-4.0 μm.
3. A method for preparing an electrocatalytically active anode film, characterized in that: The following steps are involved: The porous titanium substrate is immersed in an acidic solution for acidification to obtain a pretreated substrate; The acidified porous titanium substrate is placed in a first anodizing solution for a first anodizing, and the oxidized porous titanium substrate is placed in deionized water for ultrasonic treatment to obtain a pre-oxidized porous titanium substrate; the pre-oxidized foamed titanium substrate is placed in a second anodizing solution for a second anodizing, and ultrasonic treatment and vacuum drying are performed to obtain a porous titanium substrate with a titanium dioxide nanotube array grown thereon, which is recorded as native Ti / TiO2 NTAs; The native Ti / TiO2 NTAs are calcined to obtain a porous titanium substrate with anatase-type titanium dioxide nanotube arrays grown thereon, which is referred to as Ti / TiO2 NTAs; The Ti / TiO2 NTAs are placed in a reducing solution for cathode reduction and vacuum dried to obtain Ti 3+ Porous titanium substrate doped with anatase TiO2 nanotube arrays, denoted as r-TiO2 NTAs; The r-TiO2 NTAs were placed in a RuO2 precursor solution and dried under vacuum to obtain a TiO2 NTA loaded with RuCl3. 3+ Porous titanium substrate with doped anatase TiO2 nanotube arrays; The Ti loaded with RuCl3 3+ The porous titanium substrate of the anatase-type titanium dioxide nanotube array is calcined to obtain the Ti 3+ doped anatase titanium dioxide nanotube array-ruthenium dioxide electrocatalytically active anode film, denoted as RuO2@r-TiO2 NTAs; The acidification pretreatment solution comprises an inorganic acid and water; The first anodizing solution and the second anodizing solution are composed of a soluble fluorine source, ethylene glycol and water; The reducing solution comprises an inorganic acid and water; The RuO2 precursor solution comprises a soluble ruthenium source and water.
4. The preparation method according to claim 3, characterized in that: The acidification pretreatment solution comprises hydrofluoric acid, nitric acid and water; The volume ratio of hydrofluoric acid to nitric acid is 1:2-5, and the volume ratio of hydrofluoric acid to water is 1:5-30; The temperature for the acidification pretreatment is 20-40° C., and the pretreatment time is 10-60 seconds.
5. The preparation method according to claim 3, characterized in that: The electrolyte solution for the first anodic oxidation comprises ammonium fluoride, ethylene glycol and water; The mass ratio of ammonium fluoride to water in the electrolyte solution group for the first anodization is 1:3-6, and the mass ratio of ammonium fluoride to ethylene glycol is 1:100-400; The temperature for the first anodic oxidation is 20-35° C., the oxidation time is 0.5-10 hours, the oxidation voltage is 20-100V, the cathode comprises graphite, titanium sheet or platinum sheet, and the distance between the plates is 1-4 cm.
6. The preparation method according to claim 3, characterized in that: The electrolyte solution for the second anodic oxidation comprises ammonium fluoride, ethylene glycol and water; The mass ratio of ammonium fluoride to water in the electrolyte solution group for the second anodization is 1:2-5, and the mass ratio of ammonium fluoride to ethylene glycol is 1:200-600; The temperature for the second anodic oxidation is 20-35° C., the oxidation time is 0.5-10 hours, the oxidation voltage is 20-100V, the cathode comprises graphite, titanium sheet or platinum sheet, and the distance between the plates is 1-4 cm.
7. The preparation method according to claim 3 or 6, characterized in that: The calcination temperature is 250-500° C., the heating rate to the calcination temperature is less than 10° C. / min, and the heat preservation time is 0.5-6h.
8. The preparation method according to claim 3, characterized in that: The electrolyte solution composition of the cathode reduction reaction includes concentrated sulfuric acid and water; The molar concentration of the reducing solution is 0.1 to 0.5 mol / L; The temperature for cathode reduction is 20-40° C., the reduction time is 1-20 min, and the reduction current density is 1-10 mA / cm 2 The cathode includes graphite, titanium sheet or platinum sheet, and the distance between the plates is 1 to 4 cm.
9. The preparation method according to claim 3, characterized in that: The soluble ruthenium source in the precursor solution includes ruthenium chloride trihydrate; The concentration of the soluble ruthenium source in the precursor solution is 5 to 20 mmol / L; The load temperature of the precursor solution is 20-40° C., and the load time is 12-48 hours.
10. The preparation method according to claim 3, characterized in that: The calcination temperature is 250-500° C., the heating rate to the calcination temperature is less than 10° C. / min, and the heat preservation time is 0.5-6h.
11. Use of the electrocatalytically active anode membrane according to any one of claims 1 to 2 or the electrocatalytically active anode membrane prepared by the preparation method according to any one of claims 3 to 10 in continuous flow (Flow-through) treatment of organic wastewater.
Citation Information
Patent Citations
Preparation method of autodoped modified high-conductivity TiO2 nanotube array
CN103334142A
Electrocatalytic porous titanium filter membrane with micro nano structure and preparation method thereof
CN107020074A
Preparation method of titanium dioxide nanotube-ruthenium-titanium oxide coating titanium electrode
CN107740138A
Titanium black / ruthenium oxide composite electrode as well as preparation method and application thereof
CN111170415A
Titanium dioxide nanotube array-cerium-doped lead dioxide coating filtering membrane as well as preparation method and application thereof
CN116059838A
Cited By
Electrolytic adsorption device and application thereof
CN120504372A
Electrolytic adsorption device and its application
CN120504372B
Preparation method of iron-cobalt co-doped lead dioxide electrode and application of iron-cobalt co-doped lead dioxide electrode in synergistic degradation of wastewater containing antibiotics
CN122079319A